Antimicrobial Activity and Phytochemical Screening of Buchenavia tetraphylla (Aubl.) R. A. Howard (Combretaceae: Combretoideae). (24th December 2012) - de Oliveira, Ygor Lucena Cabral; Nascimento da Silva, Luís Cláudio; da Silva, Alexandre Gomes; Macedo, Alexandre José; Araújo, Janete Magali de; Correia, Maria Tereza dos Santos; Silva, Márcia Vanusa da
Abstract : This study evaluated the antimicrobial and hemolytic activities and phytochemical constituents of hydroalcoholic extract and its fractions from Buchenavia tetraphylla leaves. Cyclohexane (BTCF), ethyl acetate (BTEF), and n-butanol-soluble (BTSBF) and non-soluble (BTNBF) fractions were obtained from a liquid-liquid partition of hydroalcoholic extract (BTHE) from B. tetraphylla leaves. The hemolytic activity of active fractions was checked. The BTHE inhibited the growth of Micrococcus luteus (MIC: 0.10 mg/mL), Pseudomonas aeruginosa (MIC: 0.20 mg/mL), Mycobacterium smegmatis (MIC: 0.39 mg/mL), Proteus vulgaris, and Staphylococcus aureus (MIC: 0.78 mg/mL for both). The more active fractions were BTCF and BTBSF. BTCF showed better potential to inhibit M. luteus (0.10 mg/mL), P. aeruginosa (0.20 mg/mL), S. enteritidis (0.39 mg/mL), and S. aureus (1.56 mg/mL). BTBSF showed the best results for M. luteus (0.10 mg/mL), M. smegmatis, B. subtilis (0.39 mg/mL for both), and P. vulgaris (0.10 mg/mL). The HC50 were greater than observed MIC: 20.30, 4.70 and 2.53 mg/mL, respectively, to BTBF, BTHE and BTCF, which. The phytochemical analysis detected the presence of flavanoids, triterpene, carbohydrate, and tannin. Our work showed for the first time the broad-spread antimicrobial activity of B. tetraphylla, which has nonhemolytic action, creating a new perspective on the interesting association of traditional and scientific knowledge.